The Role of Personality Traits Toward Organizational Commitments and Service Quality Commitments - Lee, Seungsin; Park, Jungkun; Back, Ki-Joon; Hyun, Hyowon; Lee, Suk Hyung (Frontiers in Psychology, 2020)
Service providers personality traits is one of important determinants to deliver proper service to customers to make them satisfied in service delivery. Despite numerous studies on personality traits and emotional labor, little empirical work has been conducted to investigate the causal effects of hotel middle managers’ personality traits on their commitment to the hospitality industry. Thus, this study aims to examine the effects of hotel middle managers’ personality on two dimensions of commitments: organizational commitment and service quality commitment meditated by emotional variables: emotional labor and emotional exhaustion. The sample of this study consists of 266 department managers from full-service hotels in a metropolitan city in the Southern United States. The results confirmed the significant role of hotel middle managers’ personality traits, especially expressive personality, in organizational commitment and service quality commitment. Hotel operators should foster a work setting that consistently promotes congruent emotions via regular training and screening to reducing employees’ emotional exhaustion, increasing organizational commitment and service quality commitment, ultimately, reducing employees’ turnover intentions.